FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL REMAJA DI SMA N 1 MANUFUI KABUPATEN TIMOR TENGAH UTARA - FLORA NAIBAHO (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Social growth and patterns of people's lives will greatly affect the behavior patterns and types of diseases of the adolescent age group such as unwanted pregnancies, showing a number of diseases due to sexual intercourse and alcohol abuse, all of which will determine personal life and can be a problem for families, nations and countries in Indonesia. future. (soetjiningsih). From a preliminary survey to 10 students at SMA N 1 Manufui, it was found that 80% of students were dating and engaging in sexual behavior. This study aims to identify and explain the determinants of sexual behavior in adolescents. This research method is a quantitative research using a cross sectional design. Data collection by using a questionnaire. The population in this study were 304 students with a sample of 174 students who were taken by accidental sampling. Data processing using univariate and bivariate data analysis. The results of chi square there is a significant relationship between the variables of knowledge, information media, the role of parents and the influence of peers with adolescent sexual behavior. That exposure to information media, especially social media, plays an important role in risky sexual behavior in adolescents.